2013
DOI: 10.1101/cshperspect.a015552
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T-Cell Therapy in Transplantation: Moving to the Clinic

Abstract: Regulatory T cells (Tregs) are essential to transplantation tolerance and their therapeutic efficacy is well documented in animal models. Moreover, human Tregs can be identified, isolated, and expanded in short-term ex vivo cultures so that a therapeutic product can be manufactured at relevant doses. Treg therapy is being planned at multiple transplant centers around the world. In this article, we review topics critical to effective implementation of Treg therapy in transplantation. We will address issues such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
180
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(187 citation statements)
references
References 131 publications
0
180
1
2
Order By: Relevance
“…Although it has been reported that Tregs could be used as novel immune suppressants in various settings, including transplantation, iTregs have never been considered as a source of Tregs for therapeutic purposes because of the issues related to CNS2 demethylation and Foxp3 stability (66). Because vitamin C-treated iTregs have demethylated CNS2 and express Foxp3 stably, we checked the immune suppressive potential of vitamin C-treated iTregs by using the allogeneic skin graft model.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that Tregs could be used as novel immune suppressants in various settings, including transplantation, iTregs have never been considered as a source of Tregs for therapeutic purposes because of the issues related to CNS2 demethylation and Foxp3 stability (66). Because vitamin C-treated iTregs have demethylated CNS2 and express Foxp3 stably, we checked the immune suppressive potential of vitamin C-treated iTregs by using the allogeneic skin graft model.…”
Section: Discussionmentioning
confidence: 99%
“…The favorable therapeutic profile of Tregs has led to strong interest in Treg-based cellular therapy in transplantation and autoimmune diseases (182). Adoptive transfer of Tregs suppressed inflammation and disease in EAE, NOD mice, and mouse models of IBD and SLE (59, 60, 183-185).…”
Section: Stability Of Tregsmentioning
confidence: 99%
“…Foxp3 Ï© regulatory T (Treg) 2 cells play central roles in maintaining immune homeostasis and self-tolerance, which is essential for the control of pathogenic T cell responses (2,3). Recently, Treg cells have demonstrated promising potential in clinical therapy for autoimmune diseases (4,5).…”
mentioning
confidence: 99%